Mild hypohydration impairs cycle ergometry performance in the heat: A blinded study - Adams, J. D.; Scott, D. M.; Brand, N. A.; Suh, H. G.; Seal, A. D.; McDermott, B. P.; Ganio, M. S.; Kavouras, S. A. (Scandinavian Journal of Medicine & Science in Sports, 2019)
The aim of the present study was to observe the effect of mild hypohydration on exercise performance with subjects blinded to their hydration status. Eleven male cyclists (weight 75.8 ± 6.4 kg, VO2peak: 64.9 ± 5.6 mL/kg/min, body fat: 12.0 ± 5.8%, Powermax: 409 ± 40 W) performed three sets of criterium-like cycling, consisting of 20-minute steady-state cycling (50% peak power output), each followed by a 5-km time trial at 3% grade. Following a familiarization trial, subjects completed the experimental trials, in counter-balanced fashion, on two separate occasions in dry heat (30°C, 30% rh) either hypohydrated (HYP) or euhydrated (EUH). In both trials, subjects ingested 25 mL of water every 5 minutes during the steady-state and every 1 km of the 5-km time trials. In the EUH trial, sweat losses were fully replaced via intravenous infusion of isotonic saline, while in the HYP trial, a sham IV was instrumented. Following the exercise protocol, the subjects` bodyweight was changed by -0.1 ± 0.1% and -1.8 ± 0.2% for the EUH and HYP trial, respectively (P < 0.05). During the second and third time trials, subjects averaged higher power output (309 ± 5 and 306 ± 5 W) and faster cycling speed (27.5 ± 3.0 and 27.2 ± 3.1 km/h) in the EUH trial compared to the HYP trial (Power: 287 ± 4 and 276 ± 5 W, Speed: 26.2 ± 2.9 and 25.5 ± 3.3 km/h, all P < 0.05). Core temperature (Tre) was higher in the HYP trial throughout the third steady-state and 5-km time trial (P < 0.05). These data suggest that mild hypohydration, even when subjects were unaware of their hydration state, impaired cycle ergometry performance in the heat probably due to greater thermoregulatory strain.